2019
DOI: 10.1016/j.apsb.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell membrane-camouflaged nanoparticles: a novel drug delivery system for antitumor application

Abstract: Erythrocytes (red blood cells, RBCs) are the most abundant circulating cells in the blood and have been widely used in drug delivery systems (DDS) because of their features of biocompatibility, biodegradability, and long circulating half-life. Accordingly, a “camouflage” comprised of erythrocyte membranes renders nanoparticles as a platform that combines the advantages of native erythrocyte membranes with those of nanomaterials. Following injection into the blood of animal models, the coated nanoparticles imit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
291
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(296 citation statements)
references
References 139 publications
(161 reference statements)
2
291
0
3
Order By: Relevance
“…This membrane extraction procedure requires large volumes of cells to be harvested from culture dishes or blood and tissue samples [8,22,31,48,49]. This process has been accomplished in many ways including freeze-thaw cycling [36,48,50], electroporation [51], and osmosis-based lysis coupled with physical homogenization [22,48] ( Figure 3A). For freeze-thaw techniques, cells are frozen at −80 • C and thawed at either room temperature or 37 • C in repeated cycles.…”
Section: Membrane Extractionmentioning
confidence: 99%
“…This membrane extraction procedure requires large volumes of cells to be harvested from culture dishes or blood and tissue samples [8,22,31,48,49]. This process has been accomplished in many ways including freeze-thaw cycling [36,48,50], electroporation [51], and osmosis-based lysis coupled with physical homogenization [22,48] ( Figure 3A). For freeze-thaw techniques, cells are frozen at −80 • C and thawed at either room temperature or 37 • C in repeated cycles.…”
Section: Membrane Extractionmentioning
confidence: 99%
“…In this case, the encapsulation of nanoparticles into RBCs creates a "camouflage" for them against the immune system [151]. One review [152] described, in detail, the types of nanoparticles that were already associated with the surface or loaded inside RBCs, as well as the prospects for their use in antitumor therapy.…”
Section: Nanoparticles and Erythrocytesmentioning
confidence: 99%
“…This corresponds to greatly improved circulation times, which can reach up to 120 days. Xia et al reported on a number of developments in this arena where patient-specific RBC character can be mapped onto the RBCM-NP theranostic agents (111). Further preclinical testing of such novel theranostic nanoagents for US and PA image-guided PDT is currently underway by several groups.…”
Section: Enhancing Oxygen Content In the Microenvironment Via Nanoagentsmentioning
confidence: 99%